PENDIDIKAN ZAKAT UNTUK PEMBERDAYAAN UMAT - Asmuki Asmuki; M Holil (Fakultas Tarbiyah, Universitas Ibrahimy, 2024)
Zakat was once an effective means of empowering the Ummah in the early and golden days of Islam. Then he was not optimal, even unable to empower until now. In this article, we will explain ideas about efforts to optimize the role of zakat. This article is a literature study sourced from ideas written by many people separately, then analyzed and presented into a unified whole, and conclusions are made. The results of this study show that there are two directions of education that can be carried out in zakat education for the empowerment of the people, namely education for the Muslim community about zakat, infaq, and alms (in Indonesian abbreviated as ZIS) through the process of enculturation and socialization of ZIS and education for zakat managers with material according to their respective duties on trustful management in accordance with jurisprudence and regulations so that zakat funds are in accordance with their designation.